Functional capacity, quality of life, and disability in fibrosing interstitial lung disease: Insights into pulmonary function and outcomes - Almeida, Vitória Maciel; Fallaci, Ariel Fukushima; Jezler, Sérgio Fernandes de Oliveira; Alves, Iura Gonzalez (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Objective: This study aimed to evaluate lung function, functional capacity, quality of life, functionality, and disability in individuals diagnosed with Fibrosing Interstitial Lung Disease (IFLD). Methods: The research employed a cross-sectional design and included participants with a confirmed diagnosis of IFLD. Variables under investigation included: 1. Sociodemographic factors; 2. Pulmonary Function; 3. Functional Capacity; 4. Quality of life; 5. Functioning and Disability assessed using the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0). Ethical approval for the study was obtained from the Research Ethics Committee of the State University of Bahia (UNEB). Results: The predicted and observed distances in the six-minute walk test were 545.9±45.2 and 414.5±140.3 meters, respectively. Patients classified with a modified dyspnea scale (mMRC)=4 exhibited a significantly greater impact on functionality. The WHODAS 2.0 domains of social participation and activities of daily living were most affected in IFLD patients. Statistically significant associations were found between the distance covered and WHODAS - locomotion (r=-0.46; p<0.001) as well as between the distance covered and WHODAS-self-care (r=-0.51; p<0.001). In terms of quality of life, mental health and vitality emerged as the most compromised domains. Conclusion: This study revealed a decline in lung function, functional capacity, quality of life, and overall functionality among individuals with IFLD. Notably, the most substantial impairments were identified in domains directly related to quality of life and social interaction.